SUGAR PRODUCTION AND SALE IN THE STATE OF SÃO PAULO IN THE YEARS 2021 AND 2022 - dos Anjos, Talia Fernanda Andrade; Bertaci, Moacir (Revista Interface Tecnológica, 2023)
The objective of the work is to study and analyze, through numerical data, the production and commercialization of sugar in the State of São Paulo, considering the 2020/2021 and 2021/2022 harvests. To this end, the methodology chosen was a literature review that allowed us to state that the State of São Paulo is the largest producer and marketer of sugar in the country, due to the fact that it holds 50% of the sugarcane planting area, the largest number of industries and the largest marketer and exporter of the product and its derivatives, Copersucar. In the period analyzed, there was a 17.9% reduction in sugar production due to the lack of the main raw material, sugar cane, which was used to produce ethanol due to the more favorable market, at the same time that production grew by 5%. exports of sugar and its derivatives.
Keywords: Agribusiness; Derivatives; Production